ANALISIS PEBANDINGAN KINERJA KEUANGAN PT. BANK MANDIRI Tbk. DENGAN PT. BANK RAKYAT INDONESIA Tbk. PERIODE 2011-2015 - Fazhar Sumantri (Jurnal Khatulistiwa Informatika, 2016)
Banking, especially commercial banks is at the core of the financial system of each country. The Bank is a financial institution that becomes a venue for companies, agencies - government and private entities, and individuals to save funds - funds. PT. Bank Rakyat Indonesia Tbk. (BBRI) and PT. Bank Mandiri Tbk. (BMRI) are the two giant banking companies that excel and consistently dominate the banking industry in Indonesia, but in order to assess whether or not a bank is not only seen from the value of its assets, one of the tools that can be used to assess banks are financial ratios. The purpose of this study was to analyze the comparative financial performance. Bank Mandiri Tbk. with PT. Bank Rakyat Indonesia Tbk. using financial ratios period 2011-2015.This study uses secondary data, in the form of annual financial statements of banking companies listed in Indonesia Stock Exchange period 2011 - 2015. Of the total financial performance analyzed include four ratios measured, namely EPS, PER, PBV and DER seen that the financial performance. Bank Rakyat Indonesia Tbk. dominates overall than PT. Bank Mandiri Tbk. Tests were performed using one-way ANOVA test can be partially seen that there are differences in the average financial performance of the two companies is based on PER. But simultaneously, the statistics on the test results of this study show the difference in financial performance between the two companies. These results indicate that the establishment of a portfolio consisting of both types of shares that will provide optimal results considering both these stocks have a different characteristic views of its financial performance.